2019
DOI: 10.1002/gcc.22799
|View full text |Cite
|
Sign up to set email alerts
|

Insertional oncogenesis by HPV70 revealed by multiple genomic analyses in a clinically HPV‐negative cervical cancer

Abstract: Cervical carcinogenesis, the second leading cause of cancer death in women worldwide, is caused by multiple types of human papillomaviruses (HPVs). To investigate a possible role for HPV in a cervical carcinoma that was HPV‐negative by PCR testing, we performed HPV DNA hybridization capture plus massively parallel sequencing. This detected a subgenomic, URR‐E6‐E7‐E1 segment of HPV70 DNA, a type not generally associated with cervical cancer, inserted in an intron of the B‐cell lymphoma/leukemia 11B (BCL11B) gen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 85 publications
0
1
0
Order By: Relevance
“…2 ). HPV DNA insertions usually occur in conjunction with deletion of human sequences between the human-virus DNA junction pair, and with microhomology or small DNA insertions at the junctions with no flanking repeats 21 , similar to the observations made for Tumor 5 in this study (Fig. 2 ).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…2 ). HPV DNA insertions usually occur in conjunction with deletion of human sequences between the human-virus DNA junction pair, and with microhomology or small DNA insertions at the junctions with no flanking repeats 21 , similar to the observations made for Tumor 5 in this study (Fig. 2 ).…”
Section: Discussionsupporting
confidence: 88%
“…Since the breadth of effectiveness of GP5+/GP6+ primers with less common HPV types is uncertain 22 , and some HPV-induced cancers contain integrated, subgenomic HPV DNA segments lacking the GP5+/GP6+ target segment 12 , we performed HC + SEQ on all 13 samples to define the identity and structure of HPV DNA in each 21 . HPV DNA enrichment was accomplished through the utilization of a custom-designed capture probe set, consisting of oligonucleotide probes complementary to 143 different HPV types (HPV1 through HPV143 10 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There was only few newly published paper using nanopore platform to identify HPV integration sites ( Quan et al, 2019 ; Van Arsdale et al, 2019 ). The first study revealed that using nanopore sequencing could simultaneously detect HPV infection and microbiota composition promptly and accurately.…”
Section: Discussionmentioning
confidence: 99%